Injective Modules Relative To a Preradical - Akeel Ramadan Mehdi; Dhuha Taima Adb Al-Kadhim (Al-Qadisiyah Journal of Pure Science, 2017)
The concept of ðœŒ-injective modules (where ðœŒ is a preradical) is introduced in this work as a generalization of injective modules. The definition of ðœŒ-injectivity unifies several definitions on generalizations of injectivity such as nearly injective modules and special injective modules. Many characterizations and properties of ðœŒ-injectivity are given. We study the endomorphisms rings of ðœŒ-injective modules. The results of this work unify and extend many results in the literature.